Income inequality across states in Malaysia - Tey, Nai Peng; Lai, Siow Li; Ng, Sor Tho; Goh, Kim Leng; Osman, Ahmad Farid (Malaysian Institute of Planners, 2019)
This paper examines income differentials across the 16 states/territories in Malaysia, using quantile regression of income per capita on a nationally representative sample of 24,463 households in 2014. The results show that the vast differentials in income per capita across states are attenuated after taking into account urban-rural and ethnic distribution, but remain significant. Income differentials across states vary at different levels of income, being more pronounced at the lower ends of the distributions. States and territory in the central region had the highest income. The three states in the southern regions fared better than those in the northern region (except Penang), and the eastern region as well as East Malaysia. Other variables such as level of urbanisation, the educational level, migration, employment structure, and female labour force participation may also affect income differentials across states. © 2019 by MIP.